Harnessing rice combine harvester adoption for sustainable agriculture in the Haor (wetland) ecosystem of Bangladesh - Sujan, Md. Hayder Khan; Sarker, Mou Rani; Sarkar, Md Abdur Rouf; Sultana, Monira; Rahman, Md. Sadique; Ahammad, Sharif; Khan, Maruf (Wiley, 2025)
Technology revolutionises modern agriculture. Bangladesh's agriculture still relies heavily on manual labour for most operations, lacking full mechanisation. Given the pressing need for sustainable production and ongoing food security concerns, the country urgently requires agricultural technologies adoption. This paper aims to address this knowledge gap by examining the economic viability, determinants and impacts of adopting rice combine harvesters (RCH) in the wetland ecosystem. Quantitative and qualitative data were collected from three haor districts of Bangladesh in 2023—encompassing 300 Boro rice farmers, among whom 204 were RCH adopters and 96 were non-adopters. Results revealed the use of RCH saved USD 75/ha, leading to a 6.47% decrease in total costs and a 5.06% higher gross return for adopters compared to non-adopters. Additionally, it reduced human labour use in rice farming by 24.61%. The probit model analysis revealed that adoption factors encompassed age, yield, upland cultivation, harvester availability, repair services, perceived labour scarcity mitigation, family labour usage and harvesting losses. Propensity score matching confirmed the significant impacts of RCH adoption, showing reductions in production costs (113.97–176.23 USD/ha) and labour usage (30.04–32.08 man-days/ha), along with increased net returns (444.05–503.57 USD/ha) for adopters. Major constraints to adoption identified through the constraint facing index were timely unavailability and unsatisfactory repair services, damage of straw, heavy weights and seasonal use only. Overall, RCH is cost-effective and economically viable while also mitigating climate risks in the study area. The study findings will assist in achieving the target of doubling farmers' income under Sustainable Development Goal 2.3.